The Analyzing of Social Economic Impacted By Optimalization Of Recycling Waste As Supported For Circular Economy On Community-Based Tourism In Pasaran Island - Nurul Islami, Prima Yustitia; Prihantoro, Aji Marta (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
Pasaran Island's waste has increased significantly from year to year as a result of an increase in population. In 2022 the amount of waste on Pasaran Island will reach 504.8 kg per day. Indirectly this has an impact on various issues such as social, environmental, and health. This is marked by the emergence of various local initiatives to solve environmental problems and has an impact on the emergence of various alternative livelihoods, especially for women who live on the island. One of the efforts made has an economic impact on households. In this study, this effort is seen as a form of optimizing the potential of plastic and organic waste in increasing people's income and changing the social and environmental conditions of people on Pasaran Island. This study uses a qualitative approach with the Participatory Action Research (PAR) method, which is a method that actively involves research subjects. Data collection in this study was carried out for 1 year from March 2022 to March 2023. The key informants consisted of 5 community groups and the other key informants are village officials and women's representatives who are local initiatives. The results of this study indicate that waste management, both organic and non-organic, has a significant impact on potential alternative livelihoods, especially for women (housewives). Based on the calculation of the potential economic profit from each product produced, it reaches 50% (profit). This potential can be optimized through integration with the community-based tourism model currently being developed on Pasaran Island. These conditions indirectly impact socially, economically and environmentally